ISLAMIC ISSUES IN EAST ASIA IN THE STUDIES OF EASTERN AND WESTERN SCHOLARS - Odiljon Ernazarov (Sciental Journals Publishing, 2025)
The article analyzes the history, culture, religious and philosophical teachings and sources of East Asia, the study of the spread and development of Islam in the region. This article summarizes the spread of Islam in East Asia, the adaptation of the Muslim population to the local lifestyle and culture in various historical situations and social processes.
Keywords: The Silk Road, “One Belt One Road”, “Central Asian Islam”, “Eastren Asian Islam”, Goryeosa, The Hān Kitāb, hui.